Game changing electoral reforms and party system change? An analysis of the 2020 national assembly election in South Korea - Carl Joergen Saxer (Heliyon)
The article analyses the 2020 National Assembly election in South Korea. It was the first legislative election held after President Park Geun-hye had been successfully impeached, and removed from office, in March 2017. The 2020 election was also the first election after important changes to the electoral law were made in 2019. These changes retained the low level of proportionality of the electoral system, but now allowed parties to establish so-called satellite parties only running for proportional seats. It was the first time, since democratic transition in 1987, that we saw one party establish a supermajority, and the article argues that while changes have been made to the electoral system in the past, the changes made in the lead up to the 2020 election played a significant role in establishing a clear trend towards a dominant two-party system, with increased polarization between the two largest parties also seen in the 2024 election. The article further argues that while a regional voting pattern remains present, in particular in the Honam and Youngnam regions, there has been a shift towards a focus on the swing districts in the greater capital region, and that the move towards a two-party system is likely to continue in future elections unless changes are made to the electoral system.